Bone morphogenetic protein 10 serves as a biomarker and a potential therapeutic target for endothelial dysfunction in endotoxin-induced acute lung injury - Wen-Kuang Yu; Wei-Chih Chen; Hsiao-Chin Shen; Chuan-Yen Sun; Hui-Jung Yu; Vincent Yi-Fong Su; Kuang-Yao Yang (Journal of Translational Medicine)
Abstract Background Endothelial dysfunction plays a crucial role in the development of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) in critically ill patients. Bone Morphogenetic Protein 10 (BMP10) has been demonstrated to promote cardiovascular development and cell proliferation, support endothelial quiescence, and inhibit endothelial apoptosis. Furthermore, BMP10 has been identified as a novel biomarker for predicting the severity and clinical outcomes of various disorders. However, its role in modulating endotoxin-induced ALI remains unclear. Methods C57BL/6 mice were administered lipopolysaccharide (LPS) via intratracheal instillation to induce ALI, followed by intraperitoneal injection of BMP10 as a treatment. Simultaneously, primary human pulmonary microvascular endothelial cells (HPMECs) were used to model LPS-induced endothelial dysfunction in vitro. Additionally, plasma BMP10 levels in critically ill patients with pneumonia-related acute respiratory failure (ARF) were measured using EKISA kits. Results Hematoxylin and eosin staining of murine lung sections showed that BMP10 treatment mitigated LPS-induced alveolar interstitial thickening, edema, and inflammatory cell infiltration. Immunohistochemistry, immunofluorescence (IF) staining, and Western blot analysis of murine lung tissues revealed LPS stimulation reduced the expression of VE-cadherin and the anti-apoptotic protein MCL-1. Additionally, LPS stimulation increased the levels of ICAM-1, VCAM-1, and angiopoietin-2, highlighting evidence of endothelial dysfunction. BMP10 treatment reversed these effects. IF staining and Western blot analysis of HPMECs revealed a decrease in VE-cadherin expression and an increase in ICAM-1 and VCAM-1 following LPS stimulation. These changes were reversed by BMP10 pretreatment. Moreover, Western blot analysis of murine lung homogenates and HPMECs showed that LPS stimulation decreased the expression of pSmad1/5/8, a marker of BMP10-associated canonical signaling pathway, but BMP10 treatment restored their activation. Plasma BMP10 levels measured on the day of recruitment and 2 days later were significantly higher in critically ill patients with pneumonia-related ARF who died in the hospital compared to those who survived. Conclusions BMP10 improved LPS-induced ALI by mitigating endothelial dysfunction. Additionally, plasma BMP10 serves as a biomarker for predicting mortality in critically ill patients with pneumonia-related ARF. These findings highlight the important role of BMP10 in developing new therapeutic strategies for treating ALI and ARDS.